Comparison of productive performance, gene expression, metabolic biochemical profile and economic evaluation between some layer and broiler breeds - Ghanem, H; Elseady, Y; Ibrahim, S; Ateya, A (Journal of the Hellenic Veterinary Medical Society, 2024)
The objective of this study was to explore comparative features of productive performance, gene expression, metabolic biochemical profile and economic evaluation between some layer and broiler breeds. Three breeds (Fayoumi, Dokki 4, and Gimmizi) of broiler and three breeds of layers were enrolled in this study. Gimiza and Ross breeds elicited a higher productive performance than other ones in layer and broiler chickens respectively. mRNA levels of productive (GH, IGF-I, PGAM2, and MSTN), bone (osteocalcin), reproductive (ESR) and intestinal health (CathB, gastrotropin and MUC2) markers significantly differed among broiler and layer breeds. Serum levels of cholesterol, TG, HDLP, LDLP, T3 and T4 significantly varied within and between layer and broiler breeds. Regarding economic parameters Gimiza and Ross breeds had higher total and net returns and economic efficiency than other layer and broiler breeds. However, the latter two breeds elaborated an opposite trend for total variable and fixed costs. This study revealed that the breed factor has an impact on productive performance, gene expression, serum profile and economic parameters in layers and broiler breeds. Therefore, the aforementioned parameters could be utilized for selection of favorable breed within and between chicken breeds.